PEMANFAATAN VIRTUAL REALITY UNTUK PENGEMBANGAN KECERDASAN VISUAL DAN SPASIAL ANAK DI TKIT NUSANTARA BANTEN - Masliati, Tati; Asmayawati, Asmayawati (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the use of Virtual Reality (VR) technology in developing visual and spatial intelligence in early childhood. This study involved 30 children aged 5-6 years at TKIT Nusanatara Banten who were introduced to the use of VR in visual learning. This study used an experimental method with a quantitative approach. The subjects of the study were 30 children aged 5-6 years who attended TKIT Nusanatara Banten. Data were collected through observation, visual-spatial tests, and interviews with teachers. The results showed that the use of VR significantly improved children's visual and spatial abilities, as seen from the increase in shape recognition skills, spatial orientation, and visual understanding. Therefore, VR has the potential to be an effective learning tool in early childhood education, especially in developing visual and spatial intelligence